2021
DOI: 10.3390/d13060273
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, but Not Behavioral, Evidence Supports the Distinctiveness of the Mealy Amazon Parrot in the Brazilian Atlantic Forest

Abstract: The presence of unidentified cryptic species within a species complex can obscure demographic trends of vulnerable species, impacting potential species conservation and management decisions. Previous work identified a taxonomic split between Central and South American populations of the mealy amazon (Amazona farinosa) that subsequently resulted in the elevation of these two populations to full species status (Amazona guatemalae and A. farinosa, respectively). In that study, however, a third, geographically dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 68 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…For example, a genetic study revealed cryptic diversity within the Bahama Amazon Amazona leucocephala bahamensis between populations living on two remote islands [116]. A study on the Blue-fronted Amazon suggested treating its two subspecies as separate MUs [33], and a recent study argued for MU consideration for the Atlantic Forest population of the Southern Mealy Amazon Amazona farinosa farinosa [117]. Similarly, another study on Military Macaws Ara militaris in Mexico proposed two MUs in the country based on genetic data [118].…”
Section: Species-and Genus-level Systematics and Taxonomymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a genetic study revealed cryptic diversity within the Bahama Amazon Amazona leucocephala bahamensis between populations living on two remote islands [116]. A study on the Blue-fronted Amazon suggested treating its two subspecies as separate MUs [33], and a recent study argued for MU consideration for the Atlantic Forest population of the Southern Mealy Amazon Amazona farinosa farinosa [117]. Similarly, another study on Military Macaws Ara militaris in Mexico proposed two MUs in the country based on genetic data [118].…”
Section: Species-and Genus-level Systematics and Taxonomymentioning
confidence: 99%
“…There is little evidence that dialects in Amazona parrots would isolate populations, which would eventually generate genetic differences among the populations [194]. A recent study on these species showed that their call and genetic divergence did not correspond, which indicated that vocal dialects are not the best surrogates for genetic structure in lifelong local learners like Amazona parrots [117]. A study using SNP data of Palm Cockatoos found an association between the nuclear genomic structure of the populations and vocal dialect boundaries, however, these possibly originated from the separation of populations by mountains in the late-Quaternary [138].…”
Section: Behavioural Ecologymentioning
confidence: 99%
“…A review compiles the different genetic tools available for the study of parrot evolution, biology, and conservation [20]. Examples of the useful application of these molecular approaches are the demonstration of genetic distinctiveness of isolated populations in Brazil [21], the study of population genetics of wild and captive populations in Mexico and Bolivia [22], and the identification of the geographic origin of traded individuals in Mexico [23].…”
mentioning
confidence: 99%